2004
DOI: 10.1081/imm-120034231
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK Regulates IL‐1β Induced IL‐6 Expression Through mRNA Stability in Osteoblasts

Abstract: Osteoblast-derived IL-6 functions in coupled bone turnover by supporting osteoclastogenesis favoring bone resorption instead of bone deposition. Gene regulation of IL-6 is complex occurring both at transcription and post-transcription levels. The focus of this paper is at the level of mRNA stability, which is important in IL-6 gene regulation. Using the MC3T3-E1 as an osteoblastic model, IL-6 secretion was dose dependently decreased by SB203580, a p38 MAPK inhibitor. Steady state IL-6 mRNA was decreased with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 62 publications
6
66
0
Order By: Relevance
“…This mRNA stabilization translates into a very potent synergistic IL-6 protein expression. Based on pharmacological inhibitor data, the stabilization process seems to depend on PKC, but not on p38, contrary to the earlier described modes of IL-6 mRNA stabilization [12,[15][16][17]. Moreover, the prototypical mRNA-stabilizing protein HuR is not involved.…”
Section: Page 22 Of 48mentioning
confidence: 56%
See 4 more Smart Citations
“…This mRNA stabilization translates into a very potent synergistic IL-6 protein expression. Based on pharmacological inhibitor data, the stabilization process seems to depend on PKC, but not on p38, contrary to the earlier described modes of IL-6 mRNA stabilization [12,[15][16][17]. Moreover, the prototypical mRNA-stabilizing protein HuR is not involved.…”
Section: Page 22 Of 48mentioning
confidence: 56%
“…has been previously demonstrated to stabilize multiple mRNA species, such as COX-2 [42,43,[62][63][64], IL-8 [56] and NGF [65,66]. Importantly, it has already been reported that IL-1β stabilizes IL-6 mRNA in osteoblasts [16,35], fibroblasts [9], myofibroblasts [14], astrocytes [36] and fibroblast-like synoviocytes [12], although relatively little was known about the molecular mechanisms underlying this stabilization. Moreover, other studies found no stabilization of IL-6 mRNA after IL-1β induction, but instead found that TNF-α [11] or cAMP [67] were the stabilizing agents in this instance, indicating the cell type specificity of IL-1β-mediated mRNA stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations